(untitled) (Global Journal of Management and Business Research, 2018)
The objective of this study is to investigate the impact of different biographic characteristics such as gender, age, occupational level, education etc. on the overall job satisfaction of employees who are working in banks. In the era of globalization and free market economy, a workforce is the prime and sustainable source of competitive advantage. So, for retaining a qualified workforce, ensuring their maximum satisfaction is strategically important. As job satisfaction varies from person to person based on their various personal and professional backgrounds, it is imperative to investigate that how these different biographic characteristics affect the employee job satisfaction. This understanding will help us to predict the job expectation of different biographical groups of employees and ensure maximum satisfaction of those groups. This will also help the HR managers to deal with the employees of different age and gender groups while conducting the HRM functions. To achieve the ends, 82 employees were surveyed from the ten branches of seven reputed private banks. By analyzing the data, it has been found that how the satisfaction of the employees of different age, gender and educational background varies from one another and which factors influence the groups most.